Docência universitária: um estudo sobre a experiência da Universidade Federal de Uberlândia na formação de seus professores - Vilela, Naiara Sousa (2016)
This study aims to analyze the processes of formation and professional development of university teachers, participants in continuous training activities, with regard to understanding the pedagogical practice. The questions that guided the research were: To participate in training activities and professional development, which the understanding of university teachers regarding their teaching? This problem, other questions arise: What knowledge is constructed by academics who participate in training activities? What are the contributions of the training activities for the development of professional identity of professors? The research subjects were the teachers who work in various areas of knowledge, participants of training actions provided by the Division of Teacher Education of the UFU. The research was based mainly by the following authors:Behrens, Cruz, Imbernón, Pimenta, Masetto, Marcelo Garcia, Nóvoa, Tardif and Vasconcelos. It is a qualitative study, the type action research. Data were obtained through interviews recorded with the participation of teachers in training activities, questionnaires and interviews. Action research consisted understanding of strategy, analysis and diagnosis of reality as it presents possibilities of, to understand reality, their problems and challenges, study concrete ways to modify it. The results indicated that teachers who attended the continuing education courses could understand and revise their beliefs and professional attitudes, build and rebuild knowledge and teaching identity. Thus, it was evident the need to promote training activities for academic staff, with a view to their full professional development and the improvement of their teaching practices, to highlight: the conceptions of education, public policy, planning, classroom organization, teacher-student relationship, education technologies, teaching methodologies, assessment, among other things present in the universe of teaching. In this sense, it is clear the need to establish a training culture as well as the consolidation of institutional policies of teacher professional development at the University. The consolidation of fruitful areas of continuing education that prioritize collective work, exchange of experiences and pedagogical support aimed at improving the teaching work directly reflects the socially referenced improving the quality of higher education.